The Effect of Online Learning on Mathematics Comprehension Ability in 10th Grade Senior High School - Eliza Verdianingsih; Amalia Restu Aninda; Fitri Umardiyah; Faisol Hidayatulloh (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The situation in Indonesia is currently being hit by the spread of COVID-19. A number of policies were immediately taken by the government to break the chain of the spread of COVID-19. One of the policies in the education sector taken by the government related to the COVID-19 case is Online Learning for students. Furthermore, the ability to understand mathematics is also important for students to have, because this ability is a prerequisite for someone to have mathematical problem solving abilities. This study aims to make readers aware of the effect of online learning on students' mathematical understanding abilities. This study uses a survey method directly to students in schools with quantitative descriptive research. Data collection techniques used are test and non-test techniques. The instrument used in this study was a test of the mathematical understanding ability of 10th grade high school students and a questionnaire questionnaire. The subjects of this study were the 10th grade students of MA Al-I'dadiyyah Bahrul Ulum as many as 27 students. Based on the results of hypothesis testing, the effect of online learning on mathematical understanding ability shows a significance value of 0.000 < 0.05, then o is rejected and is accepted, and the study concludes that online learning affects the mathematical understanding ability of 10th grade students of MA Al-I'dadiyyah Bahrul Ulum on matrix addition and subtraction operations.